A Low‐Cost and Environmentally Friendly Mixed Polyanionic Cathode for Sodium‐Ion Storage. Issue 2 (14th November 2019) - Song, Tianyi; Yao, Wenjiao; Kiadkhunthod, Pinit; Zheng, Yongping; Wu, Nanzhong; Zhou, Xiaolong; Tunmee, Sarayut; Sattayaporn, Suchinda; Tang, Yongbing
Abstract: Sodium‐ion batteries (NIBs) are the most promising alternatives to lithium‐ion batteries in the development of renewable energy sources. The advancement of NIBs depends on the exploration of new electrode materials and fundamental understanding of working mechanisms. Herein, via experimental and simulation methods, we develop a mixed polyanionic compound, Na2 Fe(C2 O4 )SO4 ⋅H2 O, as a cathode for NIBs. Thanks to its rigid three dimensional framework and the combined inductive effects from oxalate and sulfate, it delivered reversible Na insertion/desertion at average discharging voltages of 3.5 and 3.1 V for 500 cycles with Coulombic efficiencies of ca. 99 %. In situ synchrotron X‐ray measurements and DFT calculations demonstrate the Fe 2+ /Fe 3+ redox reactions contribute to electron compensation during Na + desertion/insertion. The study suggests mixed polyanionic frameworks may provide promising materials for Na ion storage with the merits of low cost and environmental friendliness. Abstract : Mixed and matched : A combined oxalate and sulfate cathode is prepared. The optimized sodium‐ion battery achieves reversible Na‐ion storage for 500 cycles with high Coulombic efficiencies of approximately 99 %, indicating that mixed polyanionic frameworks may provide promising materials for Na‐ion storage with the merits of low cost and environmental friendly.